The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1161/01.cir.76.5.981
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of infarct size, contraction band necrosis, and coagulation necrosis in human autopsied hearts with acute myocardial infarction after treatment with selective intracoronary thrombolysis.

Abstract: To assess the importance of contraction band necrosis (CBN) in patients with acute myocardial infarction (AMI) treated with selective intracoronary thrombolysis, CBN, coagulation necrosis, and infarct size (expressed as CBN + coagulation necrosis) were analyzed quantitatively in 16 autopsied hearts. Intracoronary thrombolysis was performed from 2 to 6 hr after the onset of AMI, and the time from the onset of AMI to death was 7 to 168 hr. Cineangiography revealed no evidence of good collateral circulation in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…5 Similar results were found in human autopsied hearts with acute MI after treatment with thrombolysis. 13 These findings from the acute phase of AMI are supported and extended by our data because biopsies were taken in the chronic healing phase 13Ϯ9 years after the index MI in 10 studied patients (28%). Likely as a result of transmural necrosis, the core infarct consisted of transmural fibrosis in nonreperfused patients, whereas the majority of early reperfused patients showed no transmural fibrosis at all with thick layers of viable myocardium even in the core infarct region.…”
Section: Reperfusion and Myocardial Scarsupporting
confidence: 84%
“…5 Similar results were found in human autopsied hearts with acute MI after treatment with thrombolysis. 13 These findings from the acute phase of AMI are supported and extended by our data because biopsies were taken in the chronic healing phase 13Ϯ9 years after the index MI in 10 studied patients (28%). Likely as a result of transmural necrosis, the core infarct consisted of transmural fibrosis in nonreperfused patients, whereas the majority of early reperfused patients showed no transmural fibrosis at all with thick layers of viable myocardium even in the core infarct region.…”
Section: Reperfusion and Myocardial Scarsupporting
confidence: 84%
“…3 Histological studies in patients and animal models of acute MI have shown that the duration of coronary artery occlusion is proportionally correlated to the size and transmural extent of myocardial scar. 4,5,26 Scar size and geometry are important determinants for the reentrant circuit geometry and may contribute to occurrence and CL of VT. 9,27 We recently demonstrated that reperfused patients referred for ablation of recurrent VT late after MI appeared to have smaller and less confluent electroanatomic scars with thick layers of surviving myocardium found at histology. Interestingly, the CL of spontaneous and induced VTs was shorter in reperfused than in nonreperfused patients, probably because of the observed differences in scar geometry after reperfusion therapy.…”
Section: Effect Of Early Reperfusion and Inducible Vtclmentioning
confidence: 99%
“…The section (3 μm thick) was stained with phosphotungstic acid hematoxylin (PTAH). CBN was identified from the appearance of a deep blue color, multiple granulations, and hypercontraction bands, as described by Matsuda et al 9 The whole area of the section was divided into 25-27 regions and photographed with a microscope (Eclipse E400, Nikon, Tokyo, Japan) at ×40 magnification. CBN-positive cells were marked using digital image editing software Photoshop ® 6.0 (Adobe Systems, San Jose, CA, USA).…”
Section: Measurement Of the Cbn Areamentioning
confidence: 99%
“…CBN is thought to spread during the first minutes of reperfusion and to contribute to development of infarct in the later phase. 5,9,10 Temporary inhibition of contraction at the onset of reperfusion results in infarct limitation. 36 Consistent with those observations, infusion of CBX for only 1 min before onset of reperfusion not only prevented CBN in the early phase, but also delayed infarct development in the late phase of reperfusion.…”
Section: Involvement Of Gjic In Spread Of Cbn and Infarct Developmentmentioning
confidence: 99%